Insect cold tolerance and repair of chill-injury at fluctuating thermal regimes: role of ion homeostasis - Kostál, V; Renault, D; Mehrabianová, A; Bastl, J (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2007)
Adults of the bug Pyrrhocoris apterus and the beetle Alphitobius diaperinus developed chill-injury slower and survived longer when they were exposed to fluctuating thermal regimes (FTRs, where periods of low temperature were alternated with periods of higher temperature on a daily basis) rather than to constant low temperatures. The extracellular (haemolymph) concentrations of potassium ions increased with significantly higher rates in the insects exposed to constant low temperatures than in those exposed to FTRs. The concentrations of magnesium and sodium ions were maintained relatively constant or decreased slightly in both thermal regimes. The loss of body water and the increase of haemolymph osmolality contributed to, but could not fully explain, the ion concentration changes, which probably resulted also from impairing the function of an active metabolic component (ion pump) at low temperatures. This explanation was supported by observing (in P. apterus) the return toward normal [K+] during the warm "recovery" period of the FTR. Collectively, the paper stresses the importance of considering the temperature fluctuations in the experimental studies on insect cold tolerance and suggests that the positive effect of the FTR on cold tolerance may consist, at least partially, in allowing the primary ion pumping systems to re-establish the ion gradients across cell membranes and epithelia during the recovery periods at a higher temperature.
Keywords: draslík; Water; hojení ran; Adaptation, Physiological; homeostáza; osmolární koncentrace; Wound Healing; hmyz; Osmolar Concentration; voda; hemolymfa; fyziologická adaptace; Cold Temperature; Insecta; Potassium; termoregulace; zvířata; Animals; Body Temperature Regulation; Hemolymph; tělesná hmotnost; Homeostasis; nízká teplota; Body Weight